(untitled) (PJDOL, 2023)
Emotional intelligence skills are the driving force for university graduates to be developed holistically. Usually the aspects of psychomotor and effective domain, especially emotional intelligence seems to be less focused on the curriculum at this stage. This study was conducted to explore the effect of prevailing curricular activities on thedevelopment of emotional intelligence among university students